Virtual reality-based exposure with 360° video as part of cognitive behavioral therapy for social anxiety disorder: a three-arm randomized controlled trial - Per Trads Ørskov; Eik Runge; Trine Theresa Holmberg Sainte-Marie; Trine Theresa Holmberg Sainte-Marie; Mathias Torp Ernst; Mathias Torp Ernst; Lars Clemmensen; Lars Clemmensen; Caroline Høier Dalsgaard; Mia Beck Lichtenstein; Mia Beck Lichtenstein; Stéphane Bouchard; et al. (Frontiers in Virtual Reality)
BackgroundSocial anxiety disorder (SAD) has a high prevalence and an early onset. It often persists well into adulthood, turning into a chronic disorder. Cognitive behavioral therapy (CBT) is effective in treating SAD, but real-life exposure conducted as part of CBT is often costly and time-consuming, and imaginary exposure might lack realism and intensity. Virtual reality (VR)-based exposure using 360° video offers a promising way to deliver exposure therapy.ObjectiveTo develop a complete psychotherapeutic treatment program including CBT with VR-based exposure using 360° videos (CBT-ExpVR) for adult patients with SAD and to test the treatment effect using the Social Interaction Anxiety Scale (SIAS) as the primary outcome.MethodsThis three-arm randomized controlled trial involved 51 participants who were recruited through self-referral. The interventions took place at Center for Digital Psychiatry in Denmark. Participants were randomized via computer program to CBT-ExpVR, CBT with in vivo exposure (CBT-Exp), or an active control group offered VR relaxation (RlxVR). Afterwards, participants assigned to RlxVR were re-randomized to one of the two CBT interventions. Allocation was not blinded.ResultsIntention-to-treat analysis showed that participants receiving CBT-ExpVR reported significantly fewer symptoms of social anxiety at post-treatment compared to pre-treatment, β = −14.89, 95% CI (−18.64, −11.14), p < 0.0001. At post-treatment, no difference in treatment effect was found between CBT-ExpVR and CBT-Exp, β = 3.643, 95% CI (−1.727, 9.013), p = 0.1839. However, CBT-ExpVR was more effective than RlxVR, β = −11.537, 95% CI (−16.163, −6.911), p < 0.0001. Dropout rates post-treatment were 16% (CBT-ExpVR), 38% (CBT-Exp), and 20% (RlxVR). No harms were registered during the study.ConclusionCBT-ExpVR represents an effective treatment for SAD comparable to standard CBT treatment. CBT-ExpVR was reported as less costly and requiring less effort by the therapist compared to CBT-Exp. Thus, VR-based exposure might pave the way for a broader implementation of exposure in psychotherapeutic interventions for social anxiety by providing easy and low-cost access to exposure scenarios.Clinical Trials Registrationhttps://clinicaltrials.gov/study/NCT03973541, identifier NCT03973541.